2018
DOI: 10.31235/osf.io/3ahtb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When Democracy Disappears: Emergency Management in Benton Harbor

Abstract: In this case study, I look at Benton Harbor, Michigan's tenure under a state-appointed "emergency manager," with extensive local powers replacing all local elected government, and a single imperative to balance the city's budget. The law, ostensibly race-neutral, wound up targeting almost all of Michigan's cities with significant black population. The law ultimately disenfranchised half the state's black population but only two percent of whites, as well as the majority of local black officials. This law inval… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 4 publications
2
24
0
Order By: Relevance
“…The interviews lasted between 1 and 2 hours and were recorded and transcribed. We developed interview questions based on our archival research of Tamina and our research on other places (Purifoy, 2021;Seamster, 2018), both to develop our understanding of the sequence of events in Tamina, and to track the frequent co-occurrence of extractive phenomena.…”
Section: Process and Research Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interviews lasted between 1 and 2 hours and were recorded and transcribed. We developed interview questions based on our archival research of Tamina and our research on other places (Purifoy, 2021;Seamster, 2018), both to develop our understanding of the sequence of events in Tamina, and to track the frequent co-occurrence of extractive phenomena.…”
Section: Process and Research Methodsmentioning
confidence: 99%
“…This research arose from a pattern of spatial relations we identified in existing case studies and research projects we pursued in seemingly disparate Black places-small rural and periurban Black towns like Princeville and Taylortown in North Carolina (Purifoy, 2021(Purifoy, , 2018 and the larger, demographically Black cities of Flint and Benton Harbor in Michigan (Seamster, 2018). Working within our "community of inquiry" (Timmermans and Tavory, 2012: 179), we observed a pattern captured in literature about race and local development.…”
Section: Why Black Towns?mentioning
confidence: 99%
“…In this, the treatment of DPS mirrored the wider disempowerment of majority-Black municipalities in Michigan through emergency management laws as enabled by a state politics of anti-Blackness (Pulido, 2016;Ranganathan, 2016;Seamster, 2018). 6 While financial crisis is common across Michigan municipalities, only 2% of the state's white population has been placed under emergency management compared to half of its Black population (Seamster, 2018). In particular, the second state takeover was used to advance the policy preferences of elite philanthropists.…”
Section: State Of Emergency: State and Philanthropic Experimentation With Detroit Schoolsmentioning
confidence: 99%
“…The law (Public Act 436) offers a wide range of quantifiable indicators for use in determining municipal financial stress, each of which is able to trigger state takeover, and provides the potential for state takeover "at the discretion of the Treasurer. As in other cases, there is emerging evidence that the state has disproportionately targeted Black communities for emergency management (Seamster 2018;Breznau and Kirkpatrick 2018). However, we still lack a rigorous examination of takeover decisions in Michigan and their consequences for public service provision.…”
Section: State Municipal Takeovers and Austerity Politicsmentioning
confidence: 99%
“…We seek to better understand the political dynamics of state takeovers and their implications for communities, and specifically for safe, affordable drinking water services. We build on previous research indicating that state takeovers have political origins and drivers and negative social and economic consequences for affected communities (e.g., Seamster 2018;Morel 2018). While state takeovers are nominally designed to help ensure the continuation of critical public services and support communities, their implementation and intersection with austerity politics can ultimately undermine these goals.…”
Section: Introductionmentioning
confidence: 99%